Influence of Bilinguism on Socio-Cognitive Personality Development - I. V. Sokolova (Образование и наука)
The paper gives an overeview of foreign studies devoted to bilinguism and its influence on socio-cognitive personality development. Experimental research conducted in the recent years has broken the myth of negative influence of childhood bilinguism. Moreover, based on the comparative analysis, the present research shows the advantages of children and adults grown up in the bilingual environment. Their advantages compared with the monolingual peers include the well-developed meta-lingual abilities and executive functions - executive control, attention, planning, concentration, rejection of inessential information - necessary for fulfilling verbal tasks and activity control. The paper emphasizes the influence of bilinguism on cognitive decentration, ability to learn foreign languages and develop higher social sensitivity regarding both verbal and non-verbal communication (i.e. interpretation of mimics, gestures, intonations), and more adequate reaction to communicative behavior of surrounding people.The author concludes that bilinguism stimulates creativity, facilitates divergent thinking necessary for observing a variety of possible solutions and creative ideas development. Bilingual skills broaden children’s mental horizons leaving them more prepared for adult life compared to their monolingual peers.